Designing Better Educators: Impact of Using Active Learning to Enhance Design Thinking Training in Higher Education - du Plessis, Yâchal (CV Sinergi Ilmu dan Publikasi, 2025)
As educational institutions work to improve the quality of their instruction in a changing environment, the need for more dynamic and interactive methods of professional learning is becoming essential. Active learning workshops support immediate changes, as well as long-term enhancements in teaching strategies. The study assessed the effects a practical, hands-on approach to design thinking training had on educators' understanding and preparedness to implement design thinking principles. Using a longitudinal, mixed-method study, data were collected through a pre- and post-workshop survey over a two-week period. The study involved Human Resources Management (HRM) educators from a selected university in South Africa. Participants were diverse in gender, aged between 18 and 69, with experience ranging from less than 1 year to over 10 years. Furthermore, the majority of participants are of Black and Indian ethnicity. The research instrument for the study included a pre- and post-test structured questionnaire, including both open- and closed-ended questions. The study emphasized the advantages of professional development workshops that use a practical, hands-on approach to learning that will have an impact on students’ success. The results of the study demonstrated that participants showed a significantly better understanding and preparedness to implement design thinking after the workshop. Furthermore, data revealed that the impact of the workshop had both immediate and long-term improvements that included practical outcomes, increased empathy, and mindset shifts.